Nontargeted Serum Lipid Profiling of Nonalcoholic Steatohepatitis by Multisegment Injection–Nonaqueous Capillary Electrophoresis–Mass Spectrometry: A Multiplexed Separation Platform for Resolving Ionic Lipids - Ly, Ritchie; Ly, Nicholas; Sasaki, Kazunori; Suzuki, Makoto; Kami, Kenjiro; Ohashi, Yoshiaki; Britz-McKibbin, Philip (Journal of proteome research, 2022)
New methods are needed for global lipid profiling due to the complex chemical structures and diverse physicochemical properties of lipids. Herein we introduce a robust data workflow to unambiguously select lipid features from serum ether extracts by multisegment injection–nonaqueous capillary electrophoresis–mass spectrometry (MSI–NACE–MS). An iterative three-stage screening strategy is developed for nontargeted lipid analyses when using multiplexed electrophoretic separations coupled to an Orbitrap mass analyzer under negative ion mode. This approach enables the credentialing of 270 serum lipid features annotated based on their accurate mass and relative migration time, including 128 ionic lipids reliably measured (median CV ≈ 13%) in most serum samples (>75%) from nonalcoholic steatohepatitis (NASH) patients (n = 85). A mobility map is introduced to classify charged lipid classes over a wide polarity range with selectivity complementary to chromatographic separations, including lysophosphatidic acids, phosphatidylcholines, phosphatidylinositols, phosphatidylethanolamines, and nonesterified fatty acids (NEFAs). Serum lipidome profiles were also used to differentiate high- from low-risk NASH patients using a k-means clustering algorithm, where elevated circulating NEFAs (e.g., palmitic acid) were associated with increased glucose intolerance, more severe liver fibrosis, and greater disease burden. MSI–NACE–MS greatly expands the metabolome coverage of conventional aqueous-based CE–MS protocols and is a promising platform for large-scale lipidomic studies.